2020
DOI: 10.12998/wjcc.v8.i14.2917
|View full text |Cite
|
Sign up to set email alerts
|

Identification of APEX2 as an oncogene in liver cancer

Abstract: BACKGROUND DNA damage is one of the critical contributors to the occurrence and development of some cancers. APEX1 and APEX2 are the most important molecules in the DNA damage, and APEX1 has been identified as a diagnostic and prognostic biomarker in liver hepatocellular carcinoma (LIHC). However, the expression of APEX2 and its functional mechanisms in LIHC are still unclear. AIM To examine the expression of APEX2 and the potential mechanism network in LIHC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Our findings on APEX2 are supported by evidence that this ZNF protein serves as a synthetic lethal target in BRCA1- and BRCA2-deficient colonic and ovarian cancer cell lines [ 28 ]. In contrast, APEX2 overexpression has been reported in liver cancer [ 29 ] and myeloma [ 30 ]. Jensen et al recently explored the expression of APEX2 in multiple cancers and indicated that this gene possesses tissue-specific characteristics [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings on APEX2 are supported by evidence that this ZNF protein serves as a synthetic lethal target in BRCA1- and BRCA2-deficient colonic and ovarian cancer cell lines [ 28 ]. In contrast, APEX2 overexpression has been reported in liver cancer [ 29 ] and myeloma [ 30 ]. Jensen et al recently explored the expression of APEX2 in multiple cancers and indicated that this gene possesses tissue-specific characteristics [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can bind to Receptor for Advanced Glycation End products (RAGE) or Toll-like receptors (TLRs), which eventually activates the nuclear transcription factor κB (NF-κB) signal transduction pathway, and upregulates various apoptotic factors to cause cell death [ 31 , 33 ]. Meanwhile, APEX1 -encoded DNA-(apurinic or apyrimidinic site) lyase has been shown to be highly expressed in a variety of tumors, including liver [ 34 ], colorectal [ 35 ], gastric [ 36 ], and non-small-cell lung cancer [ 37 ]. Gene expression profiling demonstrated that increased APE1 correlated with glioblastoma recurrence in patients [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The larger the R, the higher the correlation was. 21 In addition, the "Gene_Corr" module of TIMER2 was used to input VPS13A-related genes, and purity adjusted Spearman rank correlation test was selected to perform gene correlation analysis on VPS13A and the selected genes, and heat maps and scatter maps with partial correlation (COR) and p values in different tumors were obtained. The larger R was, the higher the correlation was.…”
Section: Gene Enrichment Analysismentioning
confidence: 99%